Bullying of the Manager and Employees' Prosocial or Antisocial Behaviors: Impacts on Equity, Responsibility Judgments, and Witnesses' Help‐Giving. (21st January 2016) - Desrumaux, Pascale; Machado, Tony; Vallery, Gérard; Michel, Lucie
Abstract: This article aims at studying how bullying acts, revictimization, and behaviors' targets influence responsibility judgments of witnesses bullying and determine help decision. According to the literature, help‐giving has various determinants such as gravity of the bullying acts and behaviors of the perpetrators and responsibility attributed to the perpetrators and to the victims often depend on behaviors. With vignettes, we examined the influence of bullying acts, victim's prosocial or antisocial behavior at work, and revictimization on equity judgments, perceived responsibility of perpetrators and victims, and help‐giving. Eight vignettes of bullying at work were submitted to 205 participants. The results showed that the situation was judged less equitable, the victim less responsible, the perpetrator more responsible, and the intention of help increased (a) when the perpetrator's acts were serious and (b) when the bullied had emitted a prosocial behavior versus an antisocial one.